ASSESSING THE ECONOMIC IMPACT OF TERRORISM ON INTERNALLY DISPLACED PERSONS (IDPS) IN NIGERIA - ``ABDULHAMEED KUNLE ALABA; ELIJAH BABASOLA AFOLABI AGBAJE (International Studies Journal)
This study investigates the economic disparities between on-camp and off-camp Internally Displaced Persons (IDPs) in Nigeria, a gap under-explored in existing research on terrorism-induced displacement. While acknowledging the established link between terrorism and ID, this study goes further by examining the economic heterogeneity within the displaced population. Through analysis of employment, income, and livelihood strategies, it reveals the unique challenges faced by On-Camp IDPs due to restricted movement and limited access to resources. Conversely, Off-Camp IDPs demonstrate greater economic agency due to their ability to engage with local markets and support networks. Despite these differences, both groups exhibit resilience through informal income generation. This study contributes to the literature by highlighting the economic disparities within the IDP population and the influence of camp settings. The proposed policy recommendations, including targeted camp-based employment initiatives, vocational training, and robust social support systems, address these disparities and promote long-term economic recovery for IDPs. By emphasizing investments in education and infrastructure, this study offers actionable strategies for policymakers and humanitarian organizations to effectively support IDPs' economic self-sufficiency and resilience.